Wobble Moments: Dialoguing With Ethical Ambiguity in Social Networks - Westbrook, Fiona (Addleton Academic Publishers, 2025)
Social networks offer researchers unique access to communities and topics of interest, but they also present complex ethical dilemmas that can unsettle traditional research paradigms. While there have been guidelines specifically developed to ethically assist researcher considerations on these platforms, the plethora of ambiguous complexities in online encounters is difficult to attend to. These uncertainties, which expand beyond the parameters of existing guidelines, can evoke the researcher ‘wobble moments.’ A suspending of certainty, prompted by events not easily thought of in advance that cause hesitancy and unease. Employing ‘wobble moments’ as a framework, this paper shares a series of ethical tensions the author encountered when researching in social networks. By thinking, reflecting and responding to these wobbles, the equilibrium of ‘appropriate’ ethical conduct is unsettled. When dialogued, these moments signal significant occurrences that are filled with uncertainty and simultaneous possibilities. The paper contends these moments can refine and rethink what constitutes ‘good’ ethical practices, evoking (re)newed pathways and nuanced considerations when ethically researching in social networks. Embracing the wobbly complexities in place of hierarchical and colonial steeped values, researchers can develop more collaborative and responsive ethical practices, better serving the communities they engage with.
Keywords: social networks; ethics; dialogism; researching; friend request; identity sharing